A multicentre, phase II trial of ofatumumab monotherapy in relapsed/progressive diffuse large B‐cell lymphoma. (23rd August 2013) - Coiffier, Bertrand; Radford, John; Bosly, André; Martinelli, Giovanni; Barca, Gabriela; Davies, Andrew; Decaudin, Didier; Gallop‐Evans, Eve; Padmanabhan‐Iyer, Swaminathan; Van, Koen; Wu, Ka Lung; Gupta, Ira V.; et al.
Summary This international, multicentre phase II study was conducted to assess ofatumumab, a human anti‐CD20 monoclonal antibody, in patients with relapsed/progressive diffuse large B‐cell lymphoma (DLBCL) who were ineligible for autologous stem cell transplantation (TI) or who had relapse/progression after transplantation (PT). Eighty‐one patients received ofatumumab 300 mg intravenously (IV) on Day 1, followed by seven weekly IV infusions of 1000 mg. Patients in the TI and PT groups had received a median of 3 (range, 1–7) and 5 (range, 2–7) prior therapies, respectively. One‐third of patients did not respond to the last prior therapy, and 53% had failed two or more rituximab‐containing therapies. Overall response rate was 13% for the TI group (seven partial responses) and 8% for the PT group (two complete responses). Median progression‐free survival was 2·6 months, and median duration of response was 9·5 months. The most common Grade 3–4 adverse events were neutropenia (11%), leucopenia (6%), lymphopenia (6%) and thrombocytopenia (6%). Sixteen deaths have been reported, with disease progression as the most common cause of death. In conclusion, ofatumumab monotherapy was well tolerated and provided clinical benefit to some DLBCL patients in this study. This trial was registered at www.clinicaltrials.gov (NCT00622388).